2018
DOI: 10.1111/myc.12797
|View full text |Cite
|
Sign up to set email alerts
|

Use of (1→3)‐β‐d‐glucan for diagnosis and management of invasive mycoses in HIV‐infected patients

Abstract: SummaryPeople living with HIV (PLHIV) are highly vulnerable to invasive fungal infections (IFIs) due to their immune dysfunction. Diagnosis and treatment of IFIs remain challenging due to the requirement of deep tissue sampling to visualise and culture fungi before initiating treatment. Such techniques are less practical in resource‐limited settings due to their cost and requirement of relatively invasive procedures. Hence, identification of surrogate markers for the early diagnosis and therapeutic monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Overall, the levels in our cohort were within the range of BDG levels previously reported for healthy subjects (Odabasi et al 2004;Pruller et al 2014), indicating that blood BDG levels may not consistently differentiate between those with and without HIV infection. Nevertheless, an increasing number of studies support BDG as a biomarker for microbial translocation and immune activation among those with HIV infection (Ancuta et al 2008;Hoenigl et al 2016aHoenigl et al , b, 2018Farhour et al 2018;Hoenigl 2019). By contrast, the levels of BDG in CSF in our cohort were higher as compared to the cohort that received early ART (20 pg/mL compared to 5 pg/mL) (Hoenigl et al 2016a).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Overall, the levels in our cohort were within the range of BDG levels previously reported for healthy subjects (Odabasi et al 2004;Pruller et al 2014), indicating that blood BDG levels may not consistently differentiate between those with and without HIV infection. Nevertheless, an increasing number of studies support BDG as a biomarker for microbial translocation and immune activation among those with HIV infection (Ancuta et al 2008;Hoenigl et al 2016aHoenigl et al , b, 2018Farhour et al 2018;Hoenigl 2019). By contrast, the levels of BDG in CSF in our cohort were higher as compared to the cohort that received early ART (20 pg/mL compared to 5 pg/mL) (Hoenigl et al 2016a).…”
Section: Discussionmentioning
confidence: 51%
“…(1-3)-β-D-Glucan (BDG) is a cell wall component of most fungal species and is also a common component of food products (Heldt et al 2018;Prattes et al 2014). Among PLWH and without invasive fungal infection, higher levels of BDG in serum are associated with gut barrier integrity failure and luminal content translocation, including microbes and/or endogenous fungal flora from the gastrointestinal tract into the systemic circulation, and consequently with HIV-associated immunosuppression and inflammation (Ancuta et al 2008;Hoenigl et al 2016a;Farhour et al 2018;. In line with this theory, our study team reported that BDG exhibited a strong negative correlation with the proportion of gut Lactobacillales in the distal gut microbiome (low proportion of gut Lactobacillales is an indicator of microbial translocation), and positive correlation with sCD14, the soluble form of the receptor for lipopolysaccharide (LPS) (Hoenigl et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus species and P . jirovecii , which are frequent opportunistic pathogens [ 38 40 ] and are identified as part of the lung mycobiome in HIV-infected individuals [ 37 ], were not detected in the palatine tonsil mycobiome. This result indicated that each organ has a distinct community structure and the palatine tonsil may not be an important organ for opportunistic fungal colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria and fungi are the two most abundant populations of the gut microbiome. While bacterial translocation has been a focus of HIV research for a number of years, fungal translocation recently came into focus as a driver of immune activation, persistent inflammation, and non-AIDS events (7)(8)(9)(10)(11)(12). A review included in this supplement evaluated recent literature to untangle the respective roles of circulating lipopolysaccharide (LPS) and (1->3)-B-D-Glucan (BDG), which are major components of bacterial and fungal cell walls respectively and established biomarker of bacterial and fungal translocation (Ramendra et al).…”
Section: Hiv-associated Immune Activation and Persistent Inflammationmentioning
confidence: 99%